Zero-Smart Recycle Bin : IoT-Object Detection Based Smart Trash Bin System - Azkiya Aziz, Mochamad Azkal (Multidisciplinary Applied Research and Innovation, 2023)
Inadequate global recycling rates led the world to face a worsening waste management crisis. Humans keep producing numerous tons of waste every year while the landfills of the waste remain piled up and poison the world’s health sustainability. Zero-Smart Recycle Bin is designed to promote recycling movement to achieve zero net carbon emission goals. The target of the system is notably for the environmentally conscious or recycling activist, as well as for other groups in society. This paper focuses on designing the system and discussing the proposed system. The system is designed to identify and segregate the waste into different categories such as paper, metal can, and plastic bottles. The device is designed to be operated automatically using Raspberry Pi3 due to The efficiency of the processor and the compatibility with the network . The Raspberry Pi3 is integrated with object visual detection by using YOLOv5 and inductive-capacitive sensors to identify the material of the waste. The system also involves an integrated web application as the user platform. The research has achieved in proposing the design of the system, however the realization of the system design into a real product yet is still beyond of this research. Further study is aviseably required to verify and test the proposed framework and algorithm to get more desired result in the future.